Manajemen Kinerja Sekretariat Daerah Kabupaten Halmahera Barat Terkait Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP) - Mangar, Jembris; Mingkid, Elfie; Kawung, Evelin (JURNAL ADMINISTRASI PUBLIK, 2021)
Performance management is adapted into a government agency performance accountability system which includes a systematic and continuous process. The implementation of a performance accountability system for government agencies which includes performance planning, performance measurement, performance reporting, and performance evaluation, which aims to increase accountability for government performance. This research was conducted by analyzing the performance management of the West Halmahera District Secretariat related to the Government Agency Performance Accountability System (SAKIP) which is associated with the performance management cycle theory approach (The Performance Management Cycle). In this study using a qualitative research type. The data collection procedure in this research is by interviewing 7 (seven) selected informants and documents related to the issues raised. Data analysis was carried out by means of data reduction, data presentation and drawing conclusions or data verification. The results of the research obtained are that the Regional Secretariat of West Halmahera Regency has implemented the concept of performance management, but so far each stage is still not optimal, such as the low quality of performance planning documents, performance measurement is not on target, slow performance reporting and internal performance evaluation is not optimal so that the performance accountability of the Regional Secretariat of West Halmahera Regency has not been satisfactory. Efforts or strategies to increase the performance accountability of the Regional Secretariat of West Halmahera Regency, namely by improving the quality of performance planning documents, implementing technical training / guidance to improve the quality of human resources, and more often carrying out internal evaluations with the aim of following up quickly on any recommendations from the results of work program evaluations. Keywords: Performance Management. SAKIP